2010
DOI: 10.1001/archoto.2010.62
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Detection With Hematoxylin-Eosin Staining

Abstract: Hematoxylin-eosin staining of surgical specimens is a reliable and available method for the detection of bacterial biofilm in chronic infectious disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 12 publications
4
64
1
4
Order By: Relevance
“…According to recently published data of Hochstim et al, we have also conWrmed that the wide availability of H.E. and Gram staining through routine histopathology laboratories makes this a reliable method for detection of bioWlms in the clinical practice [15,16].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…According to recently published data of Hochstim et al, we have also conWrmed that the wide availability of H.E. and Gram staining through routine histopathology laboratories makes this a reliable method for detection of bioWlms in the clinical practice [15,16].…”
Section: Discussionmentioning
confidence: 73%
“…Nevertheless, bioWlms can be detected by diYcult, expensive, and time-consuming protocols of scanning electron microscopy (SEM), transmission electron microscopy (TEM), confocal laser scanning microscopy (CLSM), and recently by microbe-speciWc Xuorescent in situ hybridization (FISH) [8,13,14]. Hochstim et al [15] have reported a robust method for bioWlm detection that was based on the conventional hematoxylin-eosin (H.E.) staining of fresh surgical specimens obtained from patients with CRSwNP.…”
mentioning
confidence: 99%
“…Hematoxylin and eosin (H&E), periodic acid-Schiff (PAS), and Brown and Brenn Gram staining have been recently proposed as practical, cheap and reliable methods for detection of bacterial biofilms in different infection foci (Akiyama et al, 2003;Bulut et al, 2014;Davis et al, 2008;Hochstim et al, 2010;Oates et al, 2014;Toth et al, 2011;Winther et al, 2009;Zhang et al, 2009). The detection of biofilm by these practical and cost-effective staining methods has been used for a quantitative assessment of biofilm biomass (Bakke et al, 2001;Bulut et al, 2014;de Carvalho & da Fonseca, 2007) and could have a significant prognostic value (Hong et al, 2014).…”
Section: Microscopy Methodsmentioning
confidence: 99%
“…Moreover this technique provides highly specific identification of different bacterial species but semiquantitative results. 28 Another technique to visualize biofilm's presence directly from clinical sampel is reported by Hochstim et al 35 by using hematoxylin-eosin (HE) staining. It is a reliable and available method for the detection of bacterial biofilm in chronic infectious disease.…”
Section: Fluorescence In Situ Hybridization (Fish)mentioning
confidence: 99%
“…In particular, the wide availability of HE staining of surgical specimens through clinical pathology laboratories makes this a highly practical method for detecting biofilm in clinical practice. 35 This assay can not identifiy and differentiate the bacterial composition of biofilm and just present an early screening of biofilm-related infection in clinical sampel.…”
Section: Fluorescence In Situ Hybridization (Fish)mentioning
confidence: 99%